Z-DNA-forming silencer in the first exon regulates human ADAM-12 gene expression - Ray, Bimal K; Dhar, Srijita; Shakya, Arvind; Ray, Alpana (Proceedings of the National Academy of Sciences - PNAS, 2011)
Upregulation of ADAM-12, a novel member of the multifunctional ADAM family of proteins is linked to cancer, arthritis and cardiac hypertrophy. Basal expression of ADAM-12 is very low in adult tissues but rises markedly in response to certain physiological cues, such as during pregnancy in the placenta, during development in neonatal skeletal muscle and bone and in regenerating muscle. Studies on ADAM-12 regulation have identified a highly conserved negative regulatory element (NRE) at the 5'-UTR of human ADAM-12 gene, which acts as a transcriptional repressor. The NRE contains a stretch of dinucleotide-repeat sequence that is able to adopt a Z-DNA conformation both in vitro and in vivo and interacts with hZαADAR₁, a bona fide Z-DNA-binding protein. Substitution of the dinucleotide-repeat-element with a non-Z-DNA-forming sequence inhibited NRE function. We have detected a NRE DNA-binding protein activity in several tissues where ADAM-12 expression is low while no such activity was seen in the placenta where ADAM-12 expression is high. These observations suggest that interaction of these proteins with ADAM-12 NRE is critical for transcriptional repression of ADAM-12. We also show that the Z-DNA forming transcriptional repressor element, by interacting with these putative Z-DNA-binding proteins, is involved in the maintenance of constitutive low-level expression of human ADAM-12. Together these results provide a foundation for therapeutic down-regulation of ADAM-12 in cancer, arthritis and cardiac hypertrophy.